Review of Fluconazole Properties and Analytical Methods for Its Determination - Ruela Correa, Josilene Chaves [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Taylor & Francis Inc, 2011)
Fluconazole, alpha-(2.4-diflurofenil)-alpha-(1H-triazol-1-methyl)-1H-1,2,4-triazol-1-ethanol, is an antifungal of the triazoles class. It shows activity against species of Candida sp. and it is indicated in cases of oropharyngeal candidiasis, esophageal, vaginal, and deep infection. Fluconazole is a selective inhibitor of ergosterol, a steroid exclusive of the cell membrane of fungal cells. Fluconazole is highly absorbed by the gastrointestinal tract and spreads easily by body fluids. The main adverse reactions related to the use of fluconazole are nausea, vomiting, headache, rash, abdominal pain, diarrhea, and alopecia in patients undergoing prolonged treatment with a dose of 400 mg/day. In the form of raw material, pharmaceutical formulations, or biological material, fluconazole can be determined by methods such as titration, spectrophotometry, and thin-layer, gas, and liquid chromatography. This article discusses the pharmacological and physicochemical properties of fluconazole and also the methods of analysis applied to the determination of the drug.
Keywords: Review; fluconazole; analytical methods